(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
In the present paper we have a study on some properties of quarter symmetric metric connection in P-sasakian manifold and some results on quarter symmetric metric connection, m-projective curvature tensor, con-harmonic curvature tensor and pseudo projective curvature tensor.